2017
DOI: 10.5999/aps.2017.44.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Variables Influencing the Depth of Conscious Sedation in Plastic Surgery: A Prospective Study

Abstract: BackgroundConscious sedation has been widely utilized in plastic surgery. However, inadequate research has been published evaluating adequate drug dosage and depth of sedation. In clinical practice, sedation is often inadequate or accompanied by complications when sedatives are administered according to body weight alone. The purpose of this study was to identify variables influencing the depth of sedation during conscious sedation for plastic surgery.MethodsThis prospective study evaluated 97 patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The other two studies reported sedation level for given drug dose of midazolam 42 or midazolam and ketamine. 60 They both found that sedation levels were lighter in females than in males for their given drug protocols.…”
Section: Connected Consciousness During General Anaesthesia (Response...mentioning
confidence: 97%
See 2 more Smart Citations
“…The other two studies reported sedation level for given drug dose of midazolam 42 or midazolam and ketamine. 60 They both found that sedation levels were lighter in females than in males for their given drug protocols.…”
Section: Connected Consciousness During General Anaesthesia (Response...mentioning
confidence: 97%
“…The other two studies reported sedation level for given drug dose of midazolam 42 or midazolam and ketamine. 60 All rights reserved. No reuse allowed without permission.…”
Section: Connected Consciousness During General Anaesthesia (Response...mentioning
confidence: 99%
See 1 more Smart Citation